HE RELATIONSHIP OF WORK ATTITUDE AND WORK POSITION TOWARDS WORKLOAD ON TOMATO FRUIT SORTING WORKERS IN SEMANDING VILLAGE - Meisatama, Herta (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2023)
Background: Workload is closely related to work capacity. One of the factors that affect the value of the workload is the tasks that are carried out both physically and mentally. Objective: To determine the relationship between Work Attitude and Work Position towards Workload on Tomato Fruit Sorting Workers in Semanding Village. Methods: analytic descriptive research, using cross sectional analytics research design, that is, the measurements and observations are conducted once with a total sampling technique. The subjects were 12 tomato sorting workers. This research used measurement of workload using Work Pulse Measurement. Results: The analysis results to the final condition (post) are higher than the initial conditions (pre) and the p value = 0.001. Conclusion: Based on data analysis, it can be concluded that there is a significant increase in the workload.